The Validity of Bitcoins According to the Islamic Law - Wardah Yuspin; Sakia Agia Salsabella (Law and Justice, 2021)
The presence of bitcoin invites many uncertainties, such as concerning its legality and the statement that bitcoin is not an official currency in Indonesia. Objective: This research aims to analyze the bitcoins in the perspective of the Islamic Law. Method: This research uses the literature review method. The literary materials obtained are in the form of scientific papers, online media, books, etc. that concerns the analyzed object. Findings: The circulation of bitcoin in Indonesia as a medium of exchange cannot be regarded as a currency, as it does not fulfill the terms and conditions for something to be called money. The bitcoin’s function does not commensurate with the function of money in the concept of the Islamic economy, as it tends to be a traded commodity rather than a facility of transactional exchange. In the perspective of Islamic law, the speculative use of bitcoins may bring one to the risk of violating the law on gharar (uncertainty, hazard); dharar (a transaction that may bring loss to a party); and qimar (game of chance). No authority guarantees bitcoins, and this causes harm. In conclusion, bitcoins produce more harm than good. Thus, its usage is prohibited by Islamic law. Function: This research provides an explanation of the legality of bitcoins, that may aid the Indonesian society to decide whether or not they can use bitcoins according to the law and th sharia. Novelty: There has not been any researches that study the same topic as that discussed in this article.